Middle Power’s Role in Health Diplomacy During Covid-19; The Case of Mikta Member States - Hidayatullah, Nur Luthfi (UIN Sunan Ampel Surabaya, 2021)
This article seeks to respond towards the growing skepticism questioning MIKTA’s role in middle power diplomacy during the Covid-19 pandemic era. In recent years, the middle power informal forum MIKTA, consisting of Mexico, Indonesia, South Korea, Turkey, and Australia has been accused of being dysfunctional with lack of significant contributions towards multilateralism. Moreover, during the Covid-19 pandemic, MIKTA member states struggle to resolve domestic issues such as rising infections rate and economic recession, which indicate their withdrawal from regional and multilateral affairs. This article proves otherwise. The author argues that despite facing domestic problems related to Covid-19, MIKTA member states remain committed towards multilateralism through exemplary domestic regulations and regional contributions in a new public diplomacy role MIKTA has never taken before: health diplomacy. This descriptive-quantitative research implements quasi-experimental method by selecting five states representing middle powers from various regions and examine their health diplomacy role in domestic, regional, and multilateral affairs using indicators from Neo-Liberalist and Constructivist perspectives. This article concludes that MIKTA member states’ role in health diplomacy remain essential in supporting global health diplomacy efforts during the pandemic. Domestically, Australia and South Korea’s effective Covid-19 containment policy have served as an example for other states to follow. Regionally, MIKTA member states’ assistance towards neighboring states highlight their commitment towards regional leadership. Multilaterally, all MIKTA member states have unanimously agreed on the need to support Covid-19 vaccine availability for all countries.